Resistance to MET inhibition in MET-dependent NSCLC and therapeutic activity after switching from type I to type II MET inhibitors. (January 2023) - Riedel, Richard; Fassunke, Jana; Tumbrink, Hannah L.; Scheel, Andreas H.; Heydt, Carina; Hieggelke, Lena; Scheffler, Matthias; Heimsoeth, Alena; Nogova, Lucia; Michels, Sebastian; Weber, Jan-Phillip; Fischer, Rieke N.; et al.
Abstract: Objectives: Resistance to MET inhibition occurs inevitably in MET-dependent non-small cell lung cancer and the underlying mechanisms are insufficiently understood. We describe resistance mechanisms in patients with MET exon 14 skipping mutation (METΔ ex14 ), MET amplification, and MET fusion and report treatment outcomes after switching therapy from type I to type II MET inhibitors. Materials and methods: Pre- and post-treatment biopsies were analysed by NGS (next generation sequencing), digital droplet PCR (polymerase chain reaction), and FISH (fluorescense in situ hybridization). A patient-derived xenograft model was generated in one case. Results: Of 26 patients with MET tyrosine kinase inhibitor treatment, eight had paired pre- and post-treatment biopsies (Three with MET amplification, three with MET Δ ex14, two with MET fusions ( KIF5B-MET and PRKAR2B-MET ).) In six patients, mechanisms of resistance were detected, whereas in two cases, the cause of resistance remained unclear. We found off-target resistance mechanisms in four cases with KRAS mutations and HER2 amplifications appearing. Two patients exhibited second-site MET mutations (p.D1246N and p. Y1248H). Three patients received type I and type II MET tyrosine kinase inhibitors sequentially. In two cases, further progressive disease was seen hereafter. The patient with KIF5B-MET fusion received three different MET inhibitors and showed long-lasting stable disease and a repeated response after switching therapy, respectively. Conclusion: Resistance to MET inhibition is heterogeneous with on- and off-target mechanisms occurring regardless of the initial MET aberration. Switching therapy between different types of kinase inhibitors can lead to repeated responses in cases with second-site mutations. Controlled clinical trials in this setting with larger patient numbers are needed, as evidence to date is limited to preclinical data and case series. Highlights: Resistance to MET inhibition in MET -dependent lung cancer occurs inevitably. Switching between different types of MET inhibitors might be clinically feasible. The same resistance mechanisms occur independently of the primary MET aberration. Rebiopsies are essential for treatment decision in cases of failure of MET inhibition.